Systemic Functinal Grammar (SFG) Analysis on Short story Geri, The Forgetful Elephant - Tiara Aulia; Nasution, Rara Difania; Sintia Trinanda; Tampubolon, Jonris (Journal of Classroom Action Research, 2024)
This research aims to analyse current literature in the framework of a systematic linguistic approach for grammars. Using the short story "Geri the Forgetful Gajah", ideal, textual and interpersonal meanings will be analysed. Qualitative descriptive methods have been used by researchers. The stories have been split up and analysed on the basis of SFG to produce tables. Results show that most of the texts are based on unmarked material processes and themes, thus indicating a simple but concise story style. According to the results of the metafunction analysis, the majority of texts use behavioral and relational processes with a value of 26.66%, mental and verbal processes with a value of 13.33%, and material processes with a value of 20%. The results of the textual metafunction analysis indicate that 100 % are thematic unknowns. Key Word: Sitemic Functional Grammar Analysis; Short Story